Optimization Role Commission Eradication Corruption (Corruption Eradication Commission) in Prevent Corruption Acts in Indonesia - Vivi Hayanti; Timbul Dompak (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
The goal of this study is to maximize the Corruption Eradication Commission's (KPK) ability to stop corrupt activities. Within the executive power group, the Corruption Eradication Committee (KPK) is a state institution that exercises its authority and functions independently, unaffected by other powers. This study employs a qualitative approach and descriptive research methods. The study's findings indicate that while the Corruption Eradication Commission's (KPK) performance has improved, it is still not at its best. Corruption can result in large financial losses and erode public confidence in the government.